Climate financing for climate change adaptation: the impact of financial literacy on credit and savings behaviour of smallholder farmers in rural Indonesia - Retnoningsih, Dwi; Chung, Rebecca H. (Frontiers in Environmental Science, 2025)
Rooted in the Anthropogenic Global Warming (AGW) theory, which underscores the human-induced drivers of climate instability, this study responds to the mounting financial challenges smallholder farmers face in adapting to climate change. Adapting to climate change presents mounting financial challenges for smallholder farmers, especially in developing countries where climate variability threatens agricultural productivity and economic stability. Within this context, climate financing behaviour—defined as farmers’ financial decisions explicitly aimed at managing climate-related risks—plays a critical role in building resilience. This study examines how financial literacy influences climate financing behaviour among horticultural farmers in East Java, Indonesia, with a specific focus on two adaptive strategies: accessing formal climate credit to support climate-resilient investments, and allocating post-harvest income into precautionary savings to buffer against future climate shocks. Using an Instrumental Variable (IV) approach, this study employs IV-Probit models to evaluate the effect of financial literacy on farmers’ decisions to utilize formal climate-oriented credit and engage in adaptive savings behaviour. IV-Tobit models are applied to analyze the influence of financial literacy on the amount of climate credit obtained and the volume of climate-related savings. Results indicate that financial literacy significantly increases the likelihood of adopting both climate credit and adaptive savings behaviours, although it does not significantly affect the financial volume associated with either. A disaggregated analysis shows that financial literacy enhances credit access primarily among middle-income farmers and promotes savings accumulation particularly among low-income farmers, suggesting that climate financing behaviour is moderated by income level. These findings emphasize the importance of targeted financial education and accessible climate finance instruments—such as tailored agricultural credit products and incentivized climate savings schemes—in strengthening smallholder farmers’ adaptive capacity in the face of escalating climate-related financial risks. By aligning with the Sustainable Development Goals, this study contributes to SDG 13 (Climate Action) through promoting climate-resilient behaviours and to SDG 10 (Reduced Inequalities) by highlighting differentiated impacts across income groups, thereby supporting inclusive adaptation strategies.